The effect of NaCl salinity on nitrate and ammonium uptake and kinetics in wheat (Triticum aestivum L. cv. Gamtoos) and the partial amelioration of the salinity stress by supplemental calcium - Hawkins, Heidi-Jayne (Department of Biological Sciences, 2026)
A NaCl salinity gradient of 0 to 100 mM inhibited the biomass production, moisture content and water use efficiency of both nitrate- and ammonium-supplied wheat. The biomass production of the nitrate-supplied wheat was more reduced by the salinity gradient than the biomass production of the ammonium-supplied wheat. This was due to, in part, the differential effect of NaCl (50 mM) on NO3- and NH4+ uptake. Salinity (50 mM NaCl) decreased the 15NO3- uptake, Vmax of NO3- net uptake and total N content, especially in the shoot, of nitrate-supplied wheat. The kinetic study of NO3- uptake in salinized, nitrate-supplied wheat showed that NaCl was acting as a noncompetitive inhibitor which indicated that the effect of NaCl on NO3- uptake was at the site of the NO3- transporting apparatus. The 15NH4 + uptake of ammonium-supplied wheat was not inhibited by 50 mM NaCl, while the total N content, NH4+ depletion of the nutrient medium and Vmax of NH4+ net uptake were reduced. This suggested that the stress of 50 mM NaCl increased NH40 efflux. An increase in calcium concentration (0.5 mM to 5.0 mM) but not potassium concentration (0.2 mM to 5.0 mM) caused an increase in biomass production, moisture content, plant N content, Vmax of NO3- uptake, 15NO3- content of the shoot and potassium content in salinized, nitrate-supplied wheat. In the same plants, an increase in calcium concentration partially excluded Na+ ion entry. Calcium concentration had no effect on the biomass production, moisture content, N content or 15NH4+ uptake in salinized, ammonium-supplied wheat. An increase in potassium concentration (0.2 mM to 5.0 mM) resulted in an increase in the biomass production of salinized, ammonium-supplied wheat. This increase in biomass production was not correlated with any change in the NH4+ depletion of the nutrient medium nor with changed values of Vmax or Km of NH4+ net uptake. It is suggested that the main effect of NaCl was one of membrane disruption and that high calcium concentrations (5 mM to 8 mM) ameliorated this disruption to the extent that NO3- uptake was partially restored and ion selectivity was maintained in nitrate-supplied plants.